ChemInform Abstract: Formal [4 + 1] Cycloaddition of Methylenecyclopropanes with 7‐Aryl‐1, 3, 5‐cycloheptatrienes by Triple Gold(I) Catalysis. Issue 19 (May 2015) - Wang, Yahui; Muratore, Michael E.; Rong, Zhouting; Echavarren, Antonio M.
Abstract: 7‐Aryl‐1, 3, 5‐cycloheptatrienes and methylenecyclopropanes react in a triple gold(I)‐catalyzed transformation to cyclopentenes.